Characterization on Temporal Evolution of Porosity, Permeability, and Reactive Specific Surface Based on Fractal Model During Mineral Dissolution. Issue 20 (9th October 2020) - Tan, Qigui; Kang, Yili; You, Lijun; Xu, Chengyuan
Abstract: Accurately understanding the temporal changes in hydrological properties induced by mineral dissolution is of great importance for characterization on reactive transport system in porous media. A theoretical model for characterizing the temporal evolution of rock porosity, permeability, and reactive specific surface during mineral dissolution under two different scenarios is developed with introduction of fractal dimensions of porous media. In the first scenario, dissolution rate is assumed as a linear function of temporal pore size, and changes in fractal dimensions are closely related to the time. The second scenario allows for the constant fractal dimension and an inverse relation between dissolution rate and time. The proposed model is fully verified with some published literatures, and most of results show the excellent/good fit with experimental/simulated data. The validation of the proposed model is also briefly discussed, mainly affected by reactive transport regimes. Key Points: A theoretical model for characterizing the hydrological properties induced by mineral dissolution is proposed based on fractal dimension Two different scenarios during mineral dissolution are considered to model the temporal hydrological properties with different assumption The proposed model is verified with published literatures, and most of results show the excellent/good fit with published data